Who Gets the Money? Strategic Orientations and Resource Attraction by Not-for-Profit Organizations. Issue 4 (8th August 2022) - Modi, Pratik; Sahi, Gurjeet Kaur
ABSTRACT: Not-for-profit organizations (NPOs) depend heavily on external resources to sustain their operations and program delivery. Their financial sustainability depends on their ability to attract donors' resources, which is a challenging task in the resource-scarce external environment. Our study investigates the impact of two strategic orientations – market orientation and internal market orientation – on the success of NPOs at attracting resources. Based on survey data gathered from 360 NPOs having field operations in India in the space of environment, livelihoods, and natural resource management, and using the Partial Least Square based Structural Equation Modeling (PLS-SEM) method, we find that market orientation and staff retention predict resource attraction by NPOs. Internal market orientation has an indirect impact on resource attraction through staff retention. The study also finds that bigger NPOs attract more resources than smaller ones.